Surveillance methods - Rotaru, Bianca Stefania (Eximia, 2023)
Considering that with the passage of time the manner of committing crimes, in many cases, poses serious problems regarding the possibility of probation, it was necessary to register changes in the matter of evidence in order to improve the technical possibilities of administration. Thus, by Law no. 141/1996, the Audio or Video Recordings section was introduced, widening the scope of evidence to include audio recordings and video or photo image recordings. Shortly after, namely in 2003, by Law no. 281/2003, the possibility of administering such evidence was expanded, the title of the section being Interceptions and audio or video recordings. The seat of the matter regarding evidentiary procedures: interception and recording of conversations or communications, audio-video recordings, filming is constituted by art. 91 1 -91 6 . In addition to these procedural provisions, there are also special laws that provide for access to telecommunications or IT systems as means of evidence, such as: Law no. 143/2000 on combating drug trafficking and illicit drug consumption, which provides in art. 23 that the criminal investigation body with the authorization provided by law can have access for a determined period to the telecommunications or computer systems and supervise them with the appropriate application of art. 91 1 -91 6 Criminal Procedure Code; Law no. 678/2001 on preventing and combating human trafficking and Law no. 656/2002 on the prevention and sanctioning of money laundering with similar provisions on access to telecommunications or IT systems; Law no. 78/2002 regarding the fight against corruption and Law no. 161/2003 regarding some measures to ensure transparency in the exercise of public dignities and the sanctioning of corruption shows that there is the possibility of surveillance or interception of communications, access to information systems for all types of communications, regardless of whether they are carried out through telephone lines or in another way.